2006
DOI: 10.1002/0471143030.cb0320s30
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of GLUT4 Storage Vesicles

Abstract: The immunoisolation of GLUT4‐containing vesicles from adipocytes is described in this unit. The methods involve homogenization of cells followed by differential centrifugation to provide the intracellular membranes that contain GLUT4. Subsequently, an immobilized monoclonal antibody is used for the isolation of vesicles of very high purity. The various protocols are applicable to cultured and primary adipocytes as well as skeletal muscle, the major insulin target cells expressing GLUT4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…We turned to a detergent-free, immunoadsorption method to probe the effect of GIP on the localization of the GIPR. This method has been well established in studies of GLUT4 glucose transporter trafficking in adipocytes (Bruno et al, 2016; Kandror and Pilch, 2006). Briefly, cells are broken in the absence of detergent to preserve membranes with their embedded proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We turned to a detergent-free, immunoadsorption method to probe the effect of GIP on the localization of the GIPR. This method has been well established in studies of GLUT4 glucose transporter trafficking in adipocytes (Bruno et al, 2016; Kandror and Pilch, 2006). Briefly, cells are broken in the absence of detergent to preserve membranes with their embedded proteins.…”
Section: Resultsmentioning
confidence: 99%
“…After excess uranyl acetate was removed with filter paper, the grids were examined under a transmission electron microscope (Hitachi H7600, Hitachi, Tokyo, Japan) at 80 kV. For immuno-EM, we used a modified whole-mount immuno-EM method 29 . Briefly, purified exosomes were incubated with anti-PD-L1 (or PD-L1 isotype) antibody in blocking buffer (PBS containing 1% bovine serum albumin [BSA]) for 2 h. Then, 5 μg of the exosome suspensions was applied to formvar/carbon-coated nickel grids (200 mesh) for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance is an earlier stage in the development of type 2 diabetes, and skeletal muscle, as the largest glucose consumption and insulin-sensitive organ in the human body, is responsible for the disposal of ~2/3 of postprandial blood glucose. 10,37 Therefore, it is of great significance to study the molecular mechanism of insulin resistance in skeletal muscle induced by statins. Although Hwang et al have reported that the TAZ/IRS1 axis mediates statin-induced skeletal muscle insulin resistance, 4 whether and how GGPP is involved in statin-induced skeletal muscle insulin resistance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly support the conclusion that statins cause new‐onset diabetes. Insulin resistance is an earlier stage in the development of type 2 diabetes, and skeletal muscle, as the largest glucose consumption and insulin‐sensitive organ in the human body, is responsible for the disposal of ~2/3 of postprandial blood glucose 10,37 . Therefore, it is of great significance to study the molecular mechanism of insulin resistance in skeletal muscle induced by statins.…”
Section: Discussionmentioning
confidence: 99%